Two Decades of Muhammadiyah School Management Research: Bibliometric Analysis - Hamdi, Muhammad; Fikri, Muhammad Ali (Letiges, 2024)
This study offers a concise summary of the research on the management of Muhammadiyah schools over the past two decades. Specifically, this study aimed to identify necessary research and the most recent themes regarding the management of Muhammadiyah schools. This research used a bibliometric analysis of scientific articles from Scopus and Google Scholar. This study used 930 publications to analyze productivity, influence, research performance, and scientific journals managed by universities using indicators such as impact factor, h-index, and number of citations. VOSviewer was used to analyze the keyword networks, co-author analysis, and co-reference citation analysis. Several classifications were carried out, including examining the most influential journals, cited articles, and productive and influential researchers. This study provides high-level insights into the development of research on the management of Muhammadiyah Schools, although some variations were found. First, research trends related to Muhammadiyah school management in the last 20 years have increased, although the number of articles fluctuates yearly. Second, research on Muhammadiyah school management is grouped into six clusters. Third, few articles have been published in reputable international journals. This article presents an initial extensive overview of prominent trends and prominent researchers of Muhammadiyah School management, providing a general introduction to the subject.